Ce que la sexualité dit des frontières entre handicap et maladie d’Alzheimer - Lorraine Ory (Genre, Sexualité et Société)
This article analyzes the representations of sexuality by researchers and professionals in the fields of disability and Alzheimer’s disease. Drawing from a critical literature review, the results show a difference in the framing of sexuality in these two fields. This difference is interpreted as a predominance of a social model in the field of disability studies in contrast with the medical model of the research on Alzheimer’s disease. The article then extends the analysis of the field of Alzheimer’s disease to that of dementia and explores the evolution of the representations of sexuality. This development suggests the emergence of a social model of sexuality in the field of dementia. Finally, the article calls for the decompartmentalization of research on sexuality.